Reduced Synchronization Persistence in Neural Networks Derived from Atm-Deficient Mice - Levine-Small, Noah; Yekutieli, Ziv; Aljadeff, Yonatan; Boccaletti, Stefano; Ben Jacob, Eshel; Barzilai, Ari (Frontiers in Neuroscience, 2011)
Many neurodegenerative diseases are characterized by malfunction of the DNA damage response. Therefore, it is important to understand the connection between system level neural network behavior and DNA. Neural networks drawn from genetically engineered animals, interfaced with micro-electrode arrays (MEA) allowed us to uncover the connections between networks' system level activity properties and such genome instability. We discovered that Atm protein deficiency, which in humans leads to progressive motor impairment, leads to a reduced synchronization persistence compared to wild type synchronization, after chemically imposed DNA damage. Not only does this suggest a role for DNA stability in neural network activity but also establishes an experimental paradigm for empirically determining the role a gene plays on the behavior of a neural network.